Assessment of Dysphagia after Hemiglossectomy and Radiotherapy: A Prospective Study - Dasgupta, Sohini; Samuel, Soumi (Journal of Health and Allied Sciences NU, 2022)
Background Malignancy of the tongue is a common condition affecting patients and their day-to-day activities. The tongue plays an important role in deglutition. The combination treatment modality involving surgical resection with or without reconstruction and radiation is the most commonly used modality for such lesions. This in turn has a profound impact on the quality of life of the patients owing to the nature of the treatment.Aim of the study This study aimed to assess swallowing in patients with carcinoma tongue following hemiglossectomy and radiotherapy (RT).Methodology A prospective study carried out in 20 patients who underwent hemiglossectomy with primary closure for carcinoma of the tongue followed by RT. All patients were evaluated for swallowing using the Dysphagia Handicap Index before surgery; after surgery on the 10th and 30th days; during RT after 15 fractions of radiation; and after 1, 2, and 3 months postcompletion of RT.Results The Dysphagia Handicap Index has significantly increased from the preoperative value following both surgery and RT on all follow-up visits (p < 0.001). The most severe self-reported dysphagia was noted during and after RT(p < 0.001).Conclusion This study shows that hemiglossectomy followed by primary closure with adjuvant RT has a severe negative impact on swallowing, thereby affecting the quality of life.
Keywords: dysphagia; hemiglossectomy; mouth neoplasms; radiotherapy